2006
DOI: 10.1016/j.jacc.2006.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Late Clinical Events After Clopidogrel Discontinuation May Limit the Benefit of Drug-Eluting Stents

Abstract: After the discontinuation of clopidogrel, the benefit of DES in reducing target vessel revascularization is maintained but has to be balanced against an increase in late cardiac death or nonfatal MI, possibly related to late stent thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
589
4
46

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,227 publications
(651 citation statements)
references
References 43 publications
12
589
4
46
Order By: Relevance
“…The high nonpersistence of clopidogrel and DAPT is in line with the results of the clinical trials and long‐term observational studies leading to ESC guideline recommendations on the use of antiplatelet drugs after coronary stenting for ACS 20, 21, 22, 23. DAPT should be used for at least 1 month after a bare metal stent (BMS) implantation, for at least 6 months after a drug‐eluting stent (DES) implantation and up to a maximum of 1 year, or longer in patients with a high cardiovascular and low bleeding risk, after which monotherapy with aspirin should be continued indefinitely 23.…”
Section: Discussionsupporting
confidence: 68%
“…The high nonpersistence of clopidogrel and DAPT is in line with the results of the clinical trials and long‐term observational studies leading to ESC guideline recommendations on the use of antiplatelet drugs after coronary stenting for ACS 20, 21, 22, 23. DAPT should be used for at least 1 month after a bare metal stent (BMS) implantation, for at least 6 months after a drug‐eluting stent (DES) implantation and up to a maximum of 1 year, or longer in patients with a high cardiovascular and low bleeding risk, after which monotherapy with aspirin should be continued indefinitely 23.…”
Section: Discussionsupporting
confidence: 68%
“…6 However, emerging data suggests that DESs may increase the risk of late thrombosis, and increase morbidity and mortality. 7,11 Recent data would suggest that there is a 2-fold increase in late deaths or MI after DES implantation versus BMS. 11 However, this issue is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 Recent data would suggest that there is a 2-fold increase in late deaths or MI after DES implantation versus BMS. 11 However, this issue is still controversial. Some studies suggest that DES may have an increased risk of very late thrombosis, but this may not increase overall mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no differences in cumulative rates of death or MI between patients who received DES (versus BMS), higher rates of death and MI were observed after clopidogrel discontinuation in patients receiving DES (versus BMS; 4.9% versus 1.3%, respectively) at 18-month follow-up. 20 Additionally, a recently reported observational study in 4,666 patients who were event-free at 6-and 12-month follow-ups showed that clopidogrel use was a significant predictor of lower adjusted rates of death (2% versus 5.3%; p = 0.03, and 0% versus 3.5%, p = 0.004, respectively) and death or MI (3.1% versus 7.2%; p = 0.02, and 0% versus 4.5%, p<0.001, respectively) among patients with DES at 24 months; whereas patients who received BMS demonstrated no differences in these outcomes at 12-and 24-month follow-up. These data suggest that extended clopidogrel therapy can reduce the incidence of late thrombotic events in patients who have DES placement.…”
Section: Prevention Of Late Stent Thrombosis With Drug-eluting Stent mentioning
confidence: 99%